(3cJGH GdJKHjJ Ydi GdJHjjJs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3SdjeGf Hf eMeO SMdhd GdEOdHi s)
(3ChdgG (B:s
(3GdMeO ddg Ydi GdESdGe ehabkG dWQb GdSOGO Cf GdPi Ydjg Cgd GdSfI HMLL CeVi ef GdCSfI Cf SDGd Gdedcjf ef bHQ Mb hGdEjeGf Hg aQV TgQ s
(3BNQgG (B:s
(3gPG JeGe eG CQOJ fXeg aGdMeO ddg GdPi CJeg fXeJg ddeDefjf JHUQI CQLhG Hg GdJKHjJ YfO GdJQJQI hCMeO Gddg Ydi eG jdge Ke Ydi fHjg CSde s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQIs
(3Ydi gGeT GdQSGdI HYV GdahGFO s
(3hgj bUjOI Mhd SDGd GdejJ hJdbjfg s
(3bQf GdfSN (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds